2013
DOI: 10.1017/s1744133113000157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medical malpractice liability on rate of referrals received by specialist physicians

Abstract: Using nationally representative data from the U.S., this paper analyzed the effect of a state’s medical malpractice environment on referral visits received by specialist physicians. The analytic sample included 12,839 ambulatory visits to specialist care doctors in office-based settings in the U.S. during 2003–2007. Whether the patient was referred for the visit was examined for its association with the state’s malpractice environment, assessed by the frequency and severity of paid medical malpractice claims, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
(79 reference statements)
1
15
1
Order By: Relevance
“…These results are consistent with those in the literature [2,4,5,7,16]. Surprisingly, only a small number of physicians stated that they prescribe more medications than medically indicated [4].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with those in the literature [2,4,5,7,16]. Surprisingly, only a small number of physicians stated that they prescribe more medications than medically indicated [4].…”
Section: Discussionsupporting
confidence: 91%
“…We believe this measurement issue is the major limitation of our study and indeed all studies investigating DM. We also recognise that other factors may affect DM rates, such as the enormous variation in the medical malpractice environment, and in the healthcare and welfare systems and legal institutions across countries [16]. This could also limit the generalisability of our findings.…”
Section: Study Limitationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Xu and colleagues showed that noneconomic damages caps of $250 000 were associated with a 32 percent lower likelihood of specialist referrals. There was no association with caps at higher amounts . Yang et al found that rates of vaginal birth after C‐section were significantly higher (8.0 percent) and C‐section rates were significantly lower (1.5 percent) with caps on noneconomic damages.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies (46 percent) used a difference-in-differences specification that controlled for unobservable confounders. 12,16,[27][28][29][30]32,[34][35][36]38,40,[42][43][44][45][46] Twelve studies evaluated the impact of tort reform on defensive medicine by assessing health care utilization 20,22,23,25,26,28,37,38,47,49,51,52 of which two (17 percent) used a difference-in-differences specification. 28,38 Thirteen studies studied quality of care 16,20,21,26,28,29,[33][34][35]37,41,48,54 of which five (38 percent) used a difference-in-differences specification.…”
Section: Study Characteristicsmentioning
confidence: 99%